Liver stiffness measurement by magnetic resonance elastography predicts cirrhosis and decompensation in alcohol-related liver disease. - Chen, Jingbiao; Xu, Peng; Kalutkiewicz, Kyle; Sheng, Yiyang; Warsame, Fatima; Tahboub-Amawi, Mahmoud-Adam; Li, Jiahui; Wang, Jin; Venkatesh, Sudhakar K.; Ehman, Richard L.; Shah, Vijay H.; Simonetto, Douglas A.; et al. (Abdominal Radiology, 2024)
Purpose: To evaluate magnetic resonance elastography (MRE)—based liver stiffness measurement as a biomarker to predict the onset of cirrhosis in early-stage alcohol-related liver disease (ALD) patients, and the transition from compensated to decompensated cirrhosis in ALD. Methods: Patients with ALD and at least one MRE examination between 2007 and 2020 were included in this study. Patient demographics, liver chemistries, MELD score (within 30 days of the first MRE), and alcohol abstinence history were collected from the electronic medical records. Liver stiffness and fat fraction were measured. Disease progression was assessed in the records by noting cirrhosis onset in early-stage ALD patients and decompensation in those initially presenting with compensated cirrhosis. Nomograms and cut-off values of liver stiffness, derived from Cox proportional hazards models were created to predict the likelihood of advancing to cirrhosis or decompensation. Results: A total of 182 patients (132 men, median age 57 years) were included in this study. Among 110 patients with early-stage ALD, 23 (20.9%) developed cirrhosis after a median follow-up of 6.2 years. Among 72 patients with compensated cirrhosis, 33 (45.8%) developed decompensation after a median follow-up of 4.2 years. MRE-based liver stiffness, whether considered independently or adjusted for age, alcohol abstinence, fat fraction, and sex, was a significant and independent predictor for both future cirrhosis (Hazard ratio [HR] = 2.0–2.2, p = 0.002–0.003) and hepatic decompensation (HR = 1.2–1.3, p = 0.0001–0.006). Simplified Cox models, thresholds, and corresponding nomograms were devised for practical use, excluding non-significant or biased variables. Conclusions: MRE-based liver stiffness assessment is a useful predictor for the development of cirrhosis or decompensation in patients with ALD.